2021
DOI: 10.1186/s13044-021-00099-w
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of patients with differentiated thyroid cancer and raised antithyroglobulin antibody levels: a retrospective study

Abstract: Background Thyroglobulin (Tg) is a specific tumor marker for differentiated thyroid cancer (DTC). However, in the presence of an antithyroglobulin antibody (TgAb), it becomes unreliable. The purpose of the study was to assess the long-term outcome of DTC patients with raised TgAb. Method In a retrospective study, we included patients with DTC who had raised TgAb following total thyroidectomy. We excluded patients with persistently raised Tg (≥ 1 ng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 29 publications
(66 reference statements)
1
7
0
Order By: Relevance
“…Trimboli et al [23], Kim et al [13], and Seo et al [39] observed that positive preopTgAb was associated with the risk of disease recurrence as compared to preopTgAb negative patients. While Ora et al [38] observed an association between baseline TgAb value and treatment outcome, similar to results by Soyluk et al [18] and Patell et al [40], preopTgAb had no correlation with the outcome response in our study population. According to Ora et al [28], 35.52% and 67.05% recurrence was seen in patients with baseline TgAb of <100 and 500 IU/ml, respectively.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Trimboli et al [23], Kim et al [13], and Seo et al [39] observed that positive preopTgAb was associated with the risk of disease recurrence as compared to preopTgAb negative patients. While Ora et al [38] observed an association between baseline TgAb value and treatment outcome, similar to results by Soyluk et al [18] and Patell et al [40], preopTgAb had no correlation with the outcome response in our study population. According to Ora et al [28], 35.52% and 67.05% recurrence was seen in patients with baseline TgAb of <100 and 500 IU/ml, respectively.…”
Section: Discussionsupporting
confidence: 89%
“…In such cases, alternate methods such as neck ultrasound or image explorations are sought [35]. Postoperatively, a reduction of >50% TgAb from the baseline value is indicative of a better prognosis [38]. A slow and steady decrease in the TgAb levels post-treatment suggests a good prognosis; while an increase TgAb indicates a poor prognosis [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most of the previous studies, researchers mainly focused on the relationship between the time trend of TgAb after RAIT and clinical outcome of DTC, and revealed the trend of TgAb was more important for prognosis in TgAb-positive DTC patients [12][13][14][15][16]. However, it took time to observe the time trend of TgAb.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the clinical diagnosis of thyroid tumors is still based on pathological diagnosis as the gold standard, but surgical resection treatment is an invasive test. Ultrasound-guided thyroid aspiration cytology, which is widely used in clinical practice, has partially reduced the invasiveness, but many clinical challenges are often encountered, such as small tumors that are difficult to get to the location of the tumor, small amounts of tissue or tissue damage that makes pathology difficult to make a correct diagnosis, and surgical biopsy is an absolute contraindication for patients with bleeding tendency [ 3 ]. Therefore, it is important to study new methods for noninvasive and targeted diagnosis of thyroid tumors.…”
Section: Introductionmentioning
confidence: 99%